Insulin-like growth factor (IGF) signaling in T-cell acute lymphoblastic leukemia. (December 2019) - Gusscott, Samuel; Tamiro, Francesco; Giambra, Vincenzo; Weng, Andrew P.
Abstract: T-cell acute lymphoblastic leukemia (T-ALL) is an aggressive cancer, characterized by an uncontrolled expansion and accumulation of T-cell progenitors. During leukemic progression, immature T cells grow abnormally and occupy the bone marrow compartment, thereby interfering with the production of normal blood cells. Pediatric T-ALL is curable with intensive chemotherapy, but there are significant, long-term side effects and ~20% of patients suffer relapse for which there are limited treatment options. Adult T-ALL in contrast is largely incurable and refractory/relapsed disease is common despite multi-agent chemotherapy (5-year overall survival of ~40%), and thus new therapeutic targets are needed. We have reported previously on the role of insulin-like growth factor (IGF) signaling in T-ALL, and shown that it exerts potent phenotypes in both leukemia stem cell and bulk tumor cell populations. Modulators of IGF signaling may thus prove useful in improving outcomes in patients with T-ALL. In this review, we summarize the most recent findings relating to IGF signaling in T-ALL and outline therapeutic options using clinically relevant IGF signaling modulators.